Healthcare Professionals' Perceptions and Knowledge of the USPSTF Guidelines on Breast Self-Examination. Issue 8 (August 2015) - Loh, Kah Poh; Stefan, Mihaela S.; Friderici, Jennifer; Tan, Eng Keong; Ogunneye, Owolabi; Kleppel, Reva; Stewart, James A.
<x xml:space="preserve">Abstract</x> Objectives In 2009, the US Preventive Services Task Force (USPSTF) published revised guidelines for breast cancer screening, which recommended against teaching breast self-examination (BSE). The objective of this study was to assess providers' perceptions and knowledge regarding these updated guidelines. Methods A cross-sectional survey study was administered to 205 attending and resident physicians, nurse practitioners, physician's assistants, and registered nurses working in five medical and gynecological practices affiliated with a large academic teaching hospital in western Massachusetts. The survey solicited demographic data and inquired about practitioners' perceptions and knowledge of the revised guidelines. Results Fewer than half (41.1%) of respondents correctly identified the new USPSTF guidelines for BSE. Among those who stated they were aware of guidelines, only 37.1% adhered to them. Overall, 70% report that they teach patients to perform BSE. Teaching BSE was associated with female sex (odds ratio [OR] 2.64, 95% confidence interval [CI] 1.11–6.29), a belief that BSE reduces morbidity and mortality (OR 2.91, 95% CI 1.08–7.81), and internal medicine residency (OR 0.18, 95% CI 0.06–0.59). Conclusions Knowledge of the 2009 USPSTF guidelines is suboptimal and greater efforts should be made to educate healthcare professionals about them.